THE THE EFFECT OF WORK ENVIRONMENT AND WORKLOAD ON WORK COMMITMENT ON HEALTH ADMINISTRATORS AT SUNAN KUDUS RSI, CENTRAL JAVA: Burden, Work Commitment, Work Environment - Ahmad Farid (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Al Islam Bandung, 2022)
Commitment is a condition in which workers sided with certain organizations and their goals and desires to maintain membership in their work. The middle of two thousand twenty-two. The research design uses a cross-sectional approach. The population in this study were all health administrators at Qwerty Hospital, Central Java. The sample used in this study was 150 respondents. The endogenous variable is the workload, the exogenous variable is the work environment. This research uses Structural Equating Modeling (SEM) analysis with Smart PLS software application and Special Package for Statistical Science (SPSS). Data collection is done by distributing questionnaires. There is a direct effect of the work environment on the work commitment of health administrators by 20.9% with a T-statistic value of 3.115, there is a direct effect of workload on the work commitment of health administrators by 11.4% with a T-statistic value of 2.371. Thus, this study explains that the problems that occur can be studied in this study of 99.0% of data diversity while 0.1% is explained by other components. .Keywords: Burden, Work Commitment, Work Environment